A stylistic analysis of archaeological ceramics from Evelyn (EV01) and Klein Bolayi (EV02), two 12th-13th century settlements in the Limpopo Valley, South Africa - Antonites, Alex J. (University of Pretoria, 2022)
Dissertation (MA)--University of Pretoria, 2021.